Safety, tolerability, pharmacokinetics, and pharmacodynamics of losmapimod in healthy Japanese volunteers. Issue 4 (7th May 2015) - Ino, Hiroko; Takahashi, Naoki; Terao, Takumi; Igarashi, Harue; Sarai, Nobuaki
Abstract This phase 1 study characterized the safety, tolerability, pharmacokinetics, and pharmacodynamics of losmapimod and its metabolite GSK198602 following single and repeat doses of oral losmapimod in healthy Japanese volunteers. Subjects (n = 41) received single oral doses of losmapimod (2.5, 7.5, 20 mg) or matching placebo on 3 separate days (n = 20) or losmapimod 7.5 mg or matching placebo twice daily for 14 days (n = 21). Assessments included maximum observed plasma concentration (Cmax), time to Cmax (Tmax), apparent terminal‐phase half‐life (t1/)2, area under the curve (AUC), and change in C‐reactive protein and phosphorylated heat shock protein 27 levels. No serious adverse events occurred during the study, and there were no safety concerns regarding clinical laboratory parameters, 12‐lead electrocardiogram, or vital signs. The losmapimod Tmax was 3–4 hours, and the mean t1/2 was approximately 7.9–9.0 hours, with no appreciable difference in Tmax and apparent clearance following oral dosing between dosing regimens. Single and repeat oral doses of losmapimod were well tolerated in healthy Japanese volunteers. The Tmax of GSK198602 was similar to and t1/2 was slightly longer than those of losmapimod. Approximate dose‐proportional increases in exposure to losmapimod and GSK198602 were observed in AUC with single‐dose administration. Repeat‐dose trough concentrations reached steady state within 2 days, with an observed accumulation ratio of 1.56 and 1.91 for losmapimod and GSK198602, respectively.